Closing remarks & officiating speech 13th UiTM Dental Students' Scientific Symposium 2023 / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
The need to incorporate research into dental education has grown immensely with the advancement of scientific knowledge. The implementation of scientific research and scholarly activities in dental education is crucial to uphold the advancement of oral health and to support the creation of lifelong learners. 2. We are proud that the dental undergraduate research programme has been shown to improve the academic performance of participating students. 3. For this reason, we should equip our graduate students not only with clinical skills and knowledge but also the ability to develop and understand the processes of research and to critically assess or report on new materials and methods of innovation in dentistry.